Oil and protein levels in soybean grain from different parts of the plant=Teor de óleo e proteína em grãos de soja em diferentes posições da planta - Victor Hugo Gomes Sales (Agro@mbiente On-line, 2016)
The position of the pod on the plant stem is one of several factors that influence the chemical composition of soybean grain. Interference in the final levels of protein and oil can result in errors of quantification during the sampling process, important in breeding programs. The aim of this work was to study the effect of pod position on oil and protein levels in soybean cultivars developed for low-latitude conditions. Two experiments were installed in the experimental area of the Federal University of Tocantins (UFT) in the city of Palmas, in the State of Tocantins, Brazil (TO). The experimental design used in each experiment (agricultural year) was of randomised blocks with three replications. The treatments were arranged into split lots, with 15 soybean cultivars allocated to the lots, and pod placement on the plant stem allocated to the sub-lots. There were significant differences in protein and oil content between cultivars, as well as from the different parts of the plant. The highest protein content was seen on the upper third of the stem, and the highest oil content on the middle and lower third. It is recommended therefore that, in order to select superior cultivars, the grain sampling procedure always be carried out on the same part of the plant, so as to reduce errors of quantification of the protein and oil content as a result of the position of the pods. =A posição da vagem na haste da planta constitui um dos vários fatores que influenciam a composição química dos grãos de soja. A interferência no conteúdo final de proteína e óleo pode resultar em erros de quantificação durante o processo de amostragem, importante em programas de melhoramento. Objetivou-se com este trabalho estudar o efeito da posição das vagens na planta no teor de óleo e proteína em cultivares de soja desenvolvidas para as condições de baixa latitude. Foram instalados dois experimentos na área experimental da Universidade Federal do Tocantins (UFT), no município de Palmas - TO. O delineamento experimental utilizado em cada experimento (ano agrícola) foi de blocos casualizados, com três repetições. Os tratamentos foram dispostos em esquema de parcelas subdivididas, sendo alocados nas parcelas 15 cultivares de soja; e nas subparcelas o posicionamento das vagens na haste da planta. Houve diferenças significativas para os teores de proteína e óleo entre as cultivares, bem como nas diferentes partes da planta. Os mais altos teores de proteína foram observados no terço superior, e os mais altos teores de óleo no terço médio e inferior. Assim, recomenda-se que o processo de amostragem de grãos, visando a seleção de cultivares superiores, seja realizado na mesma posição das plantas, a fim de reduzir os erros de quantificação dos teores de proteína e óleo, pelo efeito da posição das vagens.